2018
DOI: 10.1136/neurintsurg-2018-013963
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the Derivo Embolization Device for the treatment of unruptured intracranial aneurysms: a multicentric study

Abstract: Endovascular treatment of UIAs with the DED is associated with high procedural safety and adequate occlusion rates. Examinations at 1- and 2-year follow-up will provide data on the long-term safety and angiographic outcomes of this device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Improvements in the device are more likely in terms of safety compared with this series. Similar rates have also been recently reported in two small multi-centre series with 42 unruptured and 11 ruptured aneurysms treated with DED (7,12). Our results further confirmed the safety and efficacy of DED in a real-world setting and in a large series of patients.…”
Section: Resultssupporting
confidence: 89%
“…Improvements in the device are more likely in terms of safety compared with this series. Similar rates have also been recently reported in two small multi-centre series with 42 unruptured and 11 ruptured aneurysms treated with DED (7,12). Our results further confirmed the safety and efficacy of DED in a real-world setting and in a large series of patients.…”
Section: Resultssupporting
confidence: 89%
“…Among intracranial stents and flow diverters, several in vivo and ex vivo studies have already suggested that miniaturization of the stent design and the delivery system may reduce the thrombogenicity of the device. [25][26][27][28] Hence, miniaturization of the WEB system might also contribute to reduced thrombogenicity of the system. Moreover, we observed that the WEB 17 showed a reduced tendency to protrude into the parent vessel, though we did not quantify this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The need for antiplatelet therapy and risk of rebleeding due to delayed aneurysm occlusion are potential drawbacks to flow diversion that must be considered in the treatment of ruptured aneurysms, especially in the case of highly vulnerable RBAs and RDAs. The Derivo Embolization Device (Derivo) is a novel flow diverter stent that has demonstrated high procedural safety and sufficient occlusion rates in the treatment of UIAs (5). In this case series, we report our single-center experience in treating acutely RDAs and RBAs with the Derivo to evaluate safety, effectiveness, and short-term follow-up.…”
Section: Introductionmentioning
confidence: 99%